Anlotinib combined with benmelstobart as a chemo-free first-line treatment in advanced esophageal squamous cell carcinoma: an exploratory multicenter, single-arm phase II clinical trial - Meng, Xiangrui; Yang, Xiuli; Hong, Yonggui; Wang, Wenkang; Zhang, Zhiye; Xia, Jin; Chen, Yunfang; Zhou, Yue; Lu, Taiying; Song, Min; Shan, Zhengzheng; Wu, Tao; et al. (Molecular cancer, 2025)
No combined antiangiogenic and PD-1/PD-L1 blockade therapy has been investigated as a chemo-free first-line treatment for advanced esophageal squamous cell carcinoma (ESCC). This study evaluates the efficacy and safety of anlotinib combined with benmelstobart as a chemo-free treatment in previously untreated advanced ESCC, and identifies potential predictive biomarkers using next-generation sequencing (NGS). ALTER-E-003, a single-arm, open-label phase II trial, enrolled patients with advanced ESCC across five Chinese centers. Patients received oral anlotinib 12 mg daily on days 1-14 per three-week cycle, with benmelstobart 1200 mg infused on day 1 of each cycle for up to 24 months. Thereafter, patients received anlotinib maintenance therapy. Primary endpoint was objective response rate (ORR). Secondary endpoints included progression-free survival (PFS), overall survival (OS), disease control rate (DCR), duration of response (DOR), and safety. NGS and fluorescent multiplex immunohistochemistry (mIHC) were performed on tumor specimens. Of 53 screened patients, 46 completed the study. The confirmed ORR was 56.5% (95% CI 41.1-71.1), and DCR was 91.3% (95% CI 79.2-97.6). Median PFS was 15.74 months (95% CI 9.03-21.91). Treatment-related adverse events occurred in 93.5% of patients, with 28.3% experiencing grade 3 or higher events. NGS revealed a novel predictive mutational signature (TP53+/FAT1+/NOTCH3-) that was associated with better ORR (65.6% versus 11.1%, P < 0.001), longer median PFS (17.91 versus 5.32 months, P = 0.005) and improved OS (P = 0.006). First-line anlotinib-benmelstobart combination demonstrated durable responses and acceptable safety in ESCC patients. Exploratory biomarker analyses identified a TP53+/FAT1+/NOTCH3- mutational signature potentially associated with improved outcomes, though further validation in randomized trials is warranted. NCT05038813.